Welfare Effects of Capital-Market Integration in the Presence of an International Duopoly - Panagiotis I. Karavitis; Michael S. Michael (Center for Economic Studies and ifo Institute (CESifo), 2018)
We build a two-country model with an international duopoly and capital-market integration. We examine how the convergence of the cost of capital, due to its mobility, affects the welfare of each country and their joint welfare. We find that international capital mobility, which equalizes the return to capital between the two countries, reduces their joint welfare. The welfare of the host country improves for sufficiently large market size and high level of capital-market integration, while the welfare of the source country improves only in a very restrictive case with a very small market size and small differences in their initial marginal cost of capital.
Keywords: F12; F15; H21; 330; capital-market integration; imperfect competition; international duopoly